Andean Complex a proposal in the classification of mineral deposits - Guadalupe Gómez, Enrique (2005)
In the Central Cordillera of the Andes and other points there are large mineral deposits that over time have had different meanings and interpretations. In this work we allow ourselves to suggest the name of Andean Complex to deposits that have a polygenetic character, diversity of flows, ages, mineralization and others, which have made them appear in nature as a complex, due to the various events and types of superimposed mineralization and that we allow ourselves to call them Andean Complex as a type of deposit within the genetic classification of deposits. The geological characterization of this type of deposits that are common in Peru such as Morococha, Cerro de Pasco, San Cristóbal-Andaychagua, Hualgayoc and others is accompanied; in the United States to Butte, Magma Cooper and in Bolivia to Llallagua.